Entre cinema e pintura: o hibridismo no cinema de Jean-Luc Godard - Ferreira, Veruza de Morais (2018)
This research aimed to expand the existing studies regarding the relationship between cinema and painting, investigating how the symbolic form acting in the hybridism present in the films of French film director Jean-Luc Godard. The dissertation is developed in two chapters. The first chapter, entitled "From pictorial to cinematographic", focuses on cinema and its transformations concerning the ways to represent the "real", emphasizing the French New Wave and Godard’s cinema. In the second chapter, entitled “Cinema, painting and hybrid language in Jean-Luc Godard”, after defining the concept of hybridism and its applicability, regarding the use of color, to the aspects of symbolic, hybrid and intertextual representation in the cinema, the films Pierrot Le Fou (1965), Passion (1982) e Goodbye to Language (2014) are analyzed in light of Vanoye and Goliot-Lété (1994), Penafria (2009) and Rose (2003). Throughout the text, the relationship between cinema and painting in Godard's work is carried out with a view to promoting a dialogue between art and communication. Two questions guided the investigation: how does the symbolic construction of Godard's pictorial way take place? Do the pictorial elements present in the filmic narrative really propose to construct meanings and transmit real sensations like those of the Impressionist movement in the paintings? In the understanding achieved by the research, it is affirmed that symbolism and poetics are inherent in cinema and painting in the film production of Jean-Luc Godard.